Hoax management of presidential staff office: An example of government public relations strategies - Saidah, Musfiah; Rusfian, Effy Zalfiana (Faculty of Communications Science, Dr. Soetomo University, 2020)
Hoax management is a significant factor in maintaining government stability. Public Relations is necessary to respond and manage current developing issues, especially during the current era of information. Public satisfaction is dependant on how the government manages issues and ultimately increase public trust. This research employed the qualitative approach, i.e., case study research method, which describes researches carried out intensively in great detail and depth. The data were collected through unstructured observations, interviews, and documentation. This research investigated the Communication Excellence Theory proposed by Grunig and Hunt, which illustrate the symbolic processes of understanding human behaviour within an organisation. This research also studied how the concept of public relations strategies is implemented in solving the cases mentioned in this study. The results of the analysis found that, for the Presidential Staff Office, social media was essential in establishing an effective government public relations as well as to manage public issues.